Development of Marine Products Auction Information System : (Case Study: Fish Auction Place In Karanganyar, Kragan, Rembang, Central Java ) - Sri Wulandari; Ach Lutfi Jauhari (Indonesian Scientific Journal, 2022)
Information is needed at all times, where with the development of information technology in developing computerized systems to produce the right decisions in achieving goals, the Karanganyar Kragan Fish Auction Place (TPI) is a government institution in the field of Village Unit Cooperatives which functions as a place for buying and selling fishermen and bidder. The issue to be discussed is building a marine product auction information system that will manage the information dissemination process to make it more effective and efficient. The system built will also use the PHP and MySQL programming languages. The system development method used is the Prototype method. System planning uses data flow diagram (DFD) modeling, Entity Rational Diagram (ERD). Implementation or tie-in results of information systems Auctions for marine products can manage the dissemination of information on the results of auctions that have been carried out more efficiently